Over 17.5% efficiency ternary organic solar cells with enhanced photon utilization via a medium band gap non-fullerene acceptor. Issue 30 (26th July 2021) - Cao, Congcong; Lai, Hanjian; Chen, Hui; Zhu, Yulin; Pu, Mingrui; Zheng, Nan; He, Feng
Abstract : Two medium band gap NFAs are prepared and their PL emission mostly overlaps with the absorption spectrum of Y6. The photoexcitation from acceptors increases significantly due to the energy transfer. The crystallinity and morphlogy of the blend film are also optimized significantly. Abstract : The light harvesting and photocurrent generation from acceptors largely determine the photovoltaic performance of organic solar cells (OSCs). We have designed and prepared two medium band gap non-fullerene acceptors (NFAs), BTIC-EH-2ThBr and BTIC-BO-2ThBr, containing end groups with low electron affinity. The absorption spectrum and the energy level are simultaneously finely tuned through the weak electron-withdrawing end group to serve as an excellent third component in ternary organic solar cells (TOSCs). The emission spectra of BTIC-EH-2ThBr and BTIC-BO-2ThBr mostly overlap with the absorption spectrum of the Y6 film, and efficient energy transfer is achieved from BTIC-EH-2ThBr or BTIC-BO-2ThBr to Y6. A cascade in the energy alignment could also be obtained. The morphology of the PM6:Y6:BTIC-EH-2ThBr blend film has been optimized with the addition of BTIC-EH-2ThBr as a third component. The introduction of a medium band gap molecule, BTIC-EH-2ThBr, alleviates excessive aggregation behavior and the crystallinity of the PM6:Y6 blend film. In this way, a high efficiency ternary device has been obtained with improved charge separation, transportation, collection and reduced exciton recombination. Overall, a TOSC based on PM6:Y6:BTIC-EH-2ThBr delivers the highest photovoltaic performance of 17.54% with enhanced photo utilization.